ALIANYANG HOSPITAL IN PONTIANAK, WEST BORNEO, INDONESIA - Alvino Luthfie Fachriza; Agus Zulkarnaen Arief; Erna Winansih; Doni Ananda Poeger (ARCHITENSA : Architectural Design Journal, 2026)
The provision of adequate healthcare facilities is an important component in improving public health services. Type D hospitals serve as primary healthcare referral facilities, providing basic medical services at the regional level. The planning and design of hospital facilities must comply with technical and functional standards set by national healthcare regulations. This study aims to develop the planning and architectural design of a Type D hospital in Pontianak in accordance with Indonesian Ministry of Health regulations. The design applies spatial standards, medical service zoning, circulation requirements, and supporting facility standards in accordance with national hospital planning guidelines. The expected result is a hospital design that meets regulatory requirements while supporting effective and efficient healthcare services.